2019
DOI: 10.1111/jfbc.12942
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose curcumin‐loaded Eudragit L‐100‐nanocapsules in the diet of dairy sheep increases antioxidant levels and reduces lipid peroxidation in milk

Abstract: The main objective of this study was to evaluate whether the addition of curcumin‐loaded nanocapsules (prepared and characterized) in the diets of dairy sheep improved milk quality. The nanocapsules were prepared using two polymers: poly‐ε‐caprolactone (PCL) and Eudragit L‐100. The nanocapsules contained 0.25 mg/ml (Nano‐Eudragit L‐100) and 2 mg/ml (Nano‐PCL) of curcumin. Dairy sheep were divided into four groups: A (control), B (30 mg free curcumin/kg concentrate), C (3 mg Nano‐PCL/kg concentrate), and D (3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
0
30
1
Order By: Relevance
“…However, dietary curcumin supplement in the current study had no effect on Glu, TC, TG, HDL, and LDL, which might be due to the animal species and the dosage of curcumin. A study showed that different dosages of curcumin have different effects on serum biochemistry of nursing lambs and curcumin exerted few effects on hematological parameters [39] in which only 200 mg/kg curcumin increased serum levels of glucose and urea on day 30 of experiment, while both 100mg/kg and 200 mg/kg decreased serum levels of total protein and globulin and increased the cholesterol levels on days 15 and 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, dietary curcumin supplement in the current study had no effect on Glu, TC, TG, HDL, and LDL, which might be due to the animal species and the dosage of curcumin. A study showed that different dosages of curcumin have different effects on serum biochemistry of nursing lambs and curcumin exerted few effects on hematological parameters [39] in which only 200 mg/kg curcumin increased serum levels of glucose and urea on day 30 of experiment, while both 100mg/kg and 200 mg/kg decreased serum levels of total protein and globulin and increased the cholesterol levels on days 15 and 30.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown curcumin supplement can increase the serum SOD and GPX in poultry and sheep [43,44]. It is reported that low-dose curcumin-loaded Eudragit L-100-nanocapsules in the diet of dairy sheep increases antioxidant levels and reduces lipid peroxidation in milk [39]. Other studies showed the levels of MDA, and activities of lactate dehydrogenase and nitric oxide synthase were reduced, and the levels of T-AOC and GSH were enhanced when mouse fed the Mung bean flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl polymethacrylate nanocapsules are easily encapsulated, expandable, and acid-stable ( Pereira et al., 2010 ). This nanotechnology aims to improve curcumin absorption at the intestinal level, reducing the dose in feed, with slow release of the active ingredient, especially at pH above 6.0, that is, in the ruminant gut ( Pereira et al., 2010 ; Jaguezeski et al., 2019 ; Beloqui et al., 2014 ; Manjili et al., 2017 ; Yao et al., 2017 ). Jaguezeski et al.…”
Section: Introductionmentioning
confidence: 99%
“…This nanotechnology aims to improve curcumin absorption at the intestinal level, reducing the dose in feed, with slow release of the active ingredient, especially at pH above 6.0, that is, in the ruminant gut ( Pereira et al., 2010 ; Jaguezeski et al., 2019 ; Beloqui et al., 2014 ; Manjili et al., 2017 ; Yao et al., 2017 ). Jaguezeski et al. (2019) supplemented sheep with ethyl polymethacrylate (Eudragit L-100) nanocapsules loaded with curcumin (N-CU) and found that the preparation had antioxidant effects in whey and milk, thereby reducing potentially harmful oxidative reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro experiments with a Caco-2 cell line, evidence was also obtained that bovine serum albumin dextran nanoparticles (size up to 200 nm) loaded with curcumin may exert significant cellular antioxidant activity (Fan et al, 2018b). The addition of curcumin-loaded nanocapsules produced from the Eudragit L-100 polymer to the diets of dairy sheeps resulted in a higher antioxidant capacity and lower lipid peroxidation in their milk (Jaguezeski et al, 2019). Anti-inflammatory activities of different curcumin-loaded nanocomposites were also repeatedly reported (Wang et al, 2015a;Ameruoso et al, 2017;Dewangan et al, 2017;El-Naggar et al, 2019).…”
Section: Nano-curcuminmentioning
confidence: 99%